Initial Mini-Mental State and Cerebral Perfusion in Alzheimer's Disease - TUROĞLU, HALİL TURGUT; MİDİ, İPEK; ERDİL, TANJU YUSUF; ÖNEŞ, TUNÇ (SPRINGER HEIDELBERG, 2012)
The relationship between the initial mini-mental state examination (MMSE) score and cerebral perfusion was evaluated in patients with Alzheimer's disease (AD). In the study single photon emission computed tomography (SPECT) images of the brains of 40 AD patients were compared with the brain scans of 10 healthy controls. Each patient underwent MMSE analysis at initial evaluation as well as Tc-99 m hexamethylpropyleneamine oxine (HMPAO) brain SPECT. The patients were followed up for at least 42 months. The regional cerebral blood flow (rCBF) values for patients were found to be significantly decreased for all cerebral lobes compared to the control subjects and p-values were calculated to be less than 0.001 except for occipital lobes. The most statistically significant correlation between the MMSE scores and rCBF values was determined for the left temporal lobe (p < 0.0001). A significant correlation was also found for the right temporal lobe (p < 0.005). A minimal statistically significant correlation was found for the frontal lobes and the left parietal lobe (p < 0.05). The overall cerebral perfusion was decreased except in the occipital lobes in AD cases with low initial MMSE scores and there was a significant relationship between the decrease in perfusion of the temporal/frontal lobes and the left parietal lobe with the decrease in the initial MMSE scores. The most significant relationship between the decrease in the initial MMSE scores and the rCBF values was determined for the temporal lobes (especially for the left temporal lobe). It was also found that the left frontal lobe was affected from the beginning of the disease.
Keywords: Alzheimer's disease; Dementia; Tc-hexamethylpropyleneamine oxime; Single photon emission computed tomography; Mini-mental state examination score; EMISSION COMPUTED-TOMOGRAPHY; MILD COGNITIVE IMPAIRMENT; LATE-LIFE DEPRESSION; TEMPORAL-LOBE; BLOOD-FLOW; HMPAO-SPECT; DEMENTIA; DIAGNOSIS; MEMORY; DECLINE